Model Pembelajaran Koperatif Tipe Listening Team dalam Upaya Meningkatkan Hasil Belajar Ekologi Hewan - Har, Erman (Universitas Sebelas Maret, 2016)
This research aims to study the learning outcome animal ecology using cooperative learning team listening to the students of Biology Education. This research was conducted in two cycles, each cycle consisting of two meetings. The subjects were students of semester V as many as 26 people. The research instrument used to collect data in this study is the observation sheet activities of student learning, observation sheet activities of lecturers and exam animal ecology. The results showed the average value of the final exam the first cycle is 68.3 with the percentage of completeness of 63.7 % and the average value of the final exam cycle II was 80.5 with a percentage of 87.5 % mastery learning. Â The activity average of students in the first cycle 66.9 % in the second cycle an average of 83. 2 % of the student activity. This means that the average student activity in animal ecology learning through cooperative learning model Listening Team is progressing well and can increase the activity and learning outcomes of animal ecology. The implication of this research is the type cooperative learning listening team can be used in Biology Education student learning, especially in animal ecology